The formation of discontinuous gradient regimes during crack initiation in high strength steels under very high cycle fatigue. (July 2019) - Sun, Chengqi; Song, Qingyuan; Zhou, Lingling; Liu, Jialong; Wang, Yao; Wu, Xiaolei; Wei, Yujie
Graphical abstract: Highlights: Discontinuous gradient regimes are observed during crack initiation in VHCF regime. The gradient ultrafine grains result from excessive cyclic plastic deformation. The equivalent crack growth rate in FGA is in the magnitude of 10 −12 –10 −11  m/cyc. Abstract: While fatigue is ubiquitous and is responsible for a large proportion of failure in engineering structures, we understand little regarding the mechanism of crack initiation and early-stage crack growth especially for very high cycle fatigue (VHCF) behavior. We identified in this report the microstructural evolution during interior crack initiation and early growth in a martensitic stainless steel in VHCF regime by constant and variable amplitude loading method. We observed in the post-mortem samples after VHCF a discontinuous gradient layer composed of ultrafine grains and coarse grains in the fractured surfaces using both electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM). The gradient ultrafine grains are resulted from excessive cyclic plastic deformation in the vicinity of the crack origin or crack tip, which promotes the formation of crack initiation. The equivalent crack growth rate in FGA (fine granular area) is also estimated based on the "tree ring" patterns under variable amplitude loading, which is in the magnitude of 10 −12 –10 −11  m/cyc.